Dependence of the reflection spectrum of the polymer-stabilized cholesteric liquid crystal on the length of the diacrylate and monoacrylate reactive mesogen molecules. (20th July 2017) - Oh, Yonghwan; Kim, Jongyoon; Lee, Ji-Hoon
Abstract: We investigated the dependence of the reflection spectrum of the polymer-stabilized cholesteric liquid crystal (PSCLC) on the length of the diacrylate and the monoacrylate reactive mesogen (RM) molecules. The reflection bandwidth, the reflection center wavelength, and the peak reflectance of the PSCLC with a short diacrylate and a monoacrylate RM were similar to those of the pure cholesteric liquid crystal (CLC). When a longer diacrylate RM was used, the specular reflection bandwidth was broadened and the reflection center wavelength was shifted to the longer wavelength region. When a longer monoacrylate RM was used, a smaller specular reflectance and a greater diffusional reflectance from the top substrate were observed.